Analisis Kepatuhan Minum Obat TB Paru Masa Pandemi di Puskesmas Sukarami Kota Palembang Tahun 2022 - Rezi Septa Rani; Akhmad Dwi Priyatno; Ali Harokan (Fakultas Ilmu Kesehatan Universitas Katolik Musi Charitas, 2023)
Tuberculosis is one of the 10 leading causes of death and is one of the goals in the sustainability development goals (SDGs). According to the Ministry of Health, Indonesia is ranked 2nd with the highest TB sufferers in the world after India. The CDR describes how many cases of tuberculosis are affordable by the program. The achievement of the Pulmonary TB eradication target in palembang city, one of which is the achievement of the CDR number recommended by WHO of ?90% is still far from the target. The purpose of this study was to analyze the compliance of taking pulmonary TB drugs during the pandemic at the Sukarami Health Center in Palembang City in 2022. Design this research is quantitative with analytical survey methods and cross-sectional research designs. The population and samples in this study of 82 respondents were patients diagnosed with pulmonary TB at the Sukarami Health Center in Palembang City. The sampling method with total sampling was carried out on May 31 – June 18, 2022. Data collection and retrieval using questionnaires. The results of the statistical test analysis used the chi-square statistical test and logistic regression where the results showed a meaningful relationship (p value <0.05) education variables (0.000), knowledge (0.001) and family support (0.032). There was no relationship of the variables of sex (0.948), occupation (0.852), motivation (0.642), distance (0.218), family support (0.032), health worker support (0.864). From the results of multivariate statistical tests, the dominant factor of adherence to taking pulmonary TB drugs during the pandemic was obtained, namely education (p= 0.000: OR= 12.718). It is recommended to pay attention to compliance with taking pulmonary TB drugs during the pandemic by educating about the dangers of not complying with taking Pulmonary TB drugs